2014
DOI: 10.11607/jomi.3383
|View full text |Cite
|
Sign up to set email alerts
|

Settling of Abutments into Implants and Changes in Removal Torque in Five Different Implant-Abutment Connections. Part 1: Cyclic Loading

Abstract: The results of this study demonstrated that the settling amount and RTV (loss of preload) after cyclic loading were specific to the abutment type and related to the design characteristics of the implant-abutment connection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 7 publications
2
40
0
8
Order By: Relevance
“…Reverse torque loss of the abutment screw under an 800 N static load was largest in Ø 4.0 diameter implants (86%). Several recent studies reported contradicting results of preload loss along with axial displacement after loading . One study reported no significant difference of reverse torque value after loading test .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Reverse torque loss of the abutment screw under an 800 N static load was largest in Ø 4.0 diameter implants (86%). Several recent studies reported contradicting results of preload loss along with axial displacement after loading . One study reported no significant difference of reverse torque value after loading test .…”
Section: Discussionmentioning
confidence: 91%
“…Despite the superior joint stability of the ICC, increasing concerns about axial displacement of the implant abutment into the implant have been reported . During the torque tightening procedure and occlusal loading, the implant abutment is inserted into the implant, inducing axial displacement .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Then, in addition to surface roughness, secondary factors such as the material, screw head, and thread design also have to be taken into consideration [5][6][7][8] . Furthermore, several other factors can exert a major influence on screw loosening, such as the structural design of the implant connection, a poor fit with an implant-supported prosthetic crown, and occlusal loading [9][10][11][12] . Several studies have reported that occlusal forces are the most detrimental factor of screw loosening 5,13) .…”
Section: Introductionmentioning
confidence: 99%